Impact of periodontal disease on quality of life: a systematic review - Ferreira, M. C.; Dias‐Pereira, A. C.; Branco‐de‐Almeida, L. S.; Martins, C. C.; Paiva, S. M. (Journal of periodontal research, 2017)
The diagnosis of periodontal disease is commonly based on objective evaluations of the patient's medical/dental history as well as clinical and radiographic examinations. However, periodontal disease should also be evaluated subjectively through measures that quantify its impact on oral health‐related quality of life. The aim of this study was to evaluate the impact of periodontal disease on quality of life among adolescents, adults and older adults. A systematic search of the literature was performed for scientific articles published up to July 2015 using electronic databases and a manual search. Two independent reviewers performed the selection of the studies, extracted the data and assessed the methodological quality. Thirty‐four cross‐sectional studies involving any age group, except children, and the use of questionnaires for the assessment of the impact of periodontal disease on quality of life were included. Twenty‐five studies demonstrated that periodontal disease was associated with a negative impact on quality of life, with severe periodontitis exerting the most significant impact by compromising aspects related to function and esthetics. Unlike periodontitis, gingivitis was associated with pain as well as difficulties performing oral hygiene and wearing dentures. Gingivitis was also negatively correlated with comfort. The results indicate that periodontal disease may exert an impact on quality of life of individuals, with greater severity of the disease related to greater impact. Longitudinal studies with representative samples are needed to ensure validity of the findings.